2011
DOI: 10.1159/000328745
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vascular Risk Factors on the Efficacy of Rivastigmine Patch and Capsule Treatment in Alzheimer’s Disease

Abstract: Background: Vascular risk factors (VRF) may influence response to rivastigmine in Alzheimer’s disease (AD). Methods: AD patients who participated in a randomized, double-blind, placebo-controlled trial of rivastigmine patch and capsule treatment were stratified by baseline VRF status. Treatment response was evaluated using the AD Assessment Scale-cognitive subscale (ADAS-cog), AD Cooperative Study-Clinical Global Impression of Change (ADCS-CGIC) and the AD Cooperative Study-Activities of Daily Living (ADCS-ADL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It also changes the unfavorable ratio of AChE-R to AChE-S in the CNS [208,[217][218][219][220]. AD patients with vascular risk factors may demonstrate an altered response to rivastigmine treatment compared to AD patients without these risks (cognition and speech are particularly affected) [221].…”
Section: Drug Characteristics Disadvantagesmentioning
confidence: 99%
“…It also changes the unfavorable ratio of AChE-R to AChE-S in the CNS [208,[217][218][219][220]. AD patients with vascular risk factors may demonstrate an altered response to rivastigmine treatment compared to AD patients without these risks (cognition and speech are particularly affected) [221].…”
Section: Drug Characteristics Disadvantagesmentioning
confidence: 99%
“…On the ADCS-ADL, a responder can be defined as a patient who improves or is stabilized in the course of a randomized clinical trial. It is also important to identify factors that may influence the likelihood of receiving a benefit from treatment, as patients may vary in their response to treatment according to their clinical characteristics [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one previous randomized trial has indicated that following rivastigmine treatment for 26 weeks, patients with AD with vascular risk factors (VRFs) showed greater clinical benefit in cognition, activities of daily living, and disease severity than those with AD without VRFs [ 15 ]. Another recent retrospective analysis of a large international 24-week multicenter randomized double-blind placebo-and active-controlled trial also indicated the significant impact of VRF status on treatment response in AD [ 16 ]. In these studies, however, VRFs were determined using only the Modified Hachinski Ischemic Score (HIS) [ 17 ] or by assessing the presence or absence of reported VRFs at the time of screening.…”
Section: Introductionmentioning
confidence: 99%